2020
DOI: 10.1177/0004867420924101
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence estimates of mental health problems in children and adolescents with intellectual disability: A systematic review and meta-analysis

Abstract: Background: Children and adolescents with intellectual disability are at risk of developing psychiatric symptoms and disorders; yet, the estimates reported in the literature have been inconsistent, presenting a potential barrier for service planning and delivery. Sources of variability could arise from differences in measurement instruments as well as subgroup membership by severity of intellectual disability, gender and age. This systematic review aimed to address these gaps. Method: MEDLINE and PsycINFO data… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
69
0
7

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(85 citation statements)
references
References 55 publications
(131 reference statements)
1
69
0
7
Order By: Relevance
“…The inclusion criteria were (1) children with NDDs (attention-deficit hyperactivity disorder [ADHD], ASD, specific learning disorders [SLD], tic disorders, or other neurodevelopmental disorders), as classified by DSM-5, and (2) schoolaged children (from 6 to 18 years old). The exclusion criteria were (1) children with moderate or profound intellectual disabilities (because validation of CBCL in intellectual disability was uncertain in the previous study 29 , we prioritized eliminating the effects of intellectual ability on sleep patterns and mental health in this study) and (2) parents who did not understand the questionnaires written in Japanese.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The inclusion criteria were (1) children with NDDs (attention-deficit hyperactivity disorder [ADHD], ASD, specific learning disorders [SLD], tic disorders, or other neurodevelopmental disorders), as classified by DSM-5, and (2) schoolaged children (from 6 to 18 years old). The exclusion criteria were (1) children with moderate or profound intellectual disabilities (because validation of CBCL in intellectual disability was uncertain in the previous study 29 , we prioritized eliminating the effects of intellectual ability on sleep patterns and mental health in this study) and (2) parents who did not understand the questionnaires written in Japanese.…”
Section: Methodsmentioning
confidence: 99%
“…A recent online anonymous study on adults showed that the COVID-19 pandemic was negatively associated with mental health (i.e., stress and depression) and QOL [11][12][13] . A higher risk for increased anxiety and depression was seen in younger women (18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29), unemployed persons, individuals with a prior psychiatric history, and those reporting a greater negative impact on their QOL 11,12 .…”
Section: Alterations Of Child and Parent Qolmentioning
confidence: 99%
“…Auch wenn für das Erwachsenenalter mittlerweile Studienergebnisse zur psychischen Gesundheit von Menschen mit Behinderung in Deutschland vorliegen [15,16], sind für das Heranwachsendenalter kaum systematische Auswertungen basierend auf repräsentativen Surveydaten vorzufinden. Internationale Studien ergebnisse verdeutlichen, dass psychische Störungen bei Kindern und Jugendlichen mit Behinderung unabhängig von der Behinderungsart ebenfalls häufiger auftreten als bei Gleichaltrigen ohne Behinderungen [17][18][19][20][21]. Ein Review von Buckley et al [21] verdeutlicht, dass Kinder und Jugendliche im Alter von 6 bis 21 Jahren mit geistiger Behinderung im Vergleich zu jenen ohne Behinderung eine signifikant schlechtere psychische Gesundheit und Prävalenzen von psychischen Störungen zwischen 38 und 49 % aufweisen [21].…”
Section: Gesundheit Von Kindern Und Jugendlichen Mit Beeinträchtigungenunclassified
“…Internationale Studien ergebnisse verdeutlichen, dass psychische Störungen bei Kindern und Jugendlichen mit Behinderung unabhängig von der Behinderungsart ebenfalls häufiger auftreten als bei Gleichaltrigen ohne Behinderungen [17][18][19][20][21]. Ein Review von Buckley et al [21] verdeutlicht, dass Kinder und Jugendliche im Alter von 6 bis 21 Jahren mit geistiger Behinderung im Vergleich zu jenen ohne Behinderung eine signifikant schlechtere psychische Gesundheit und Prävalenzen von psychischen Störungen zwischen 38 und 49 % aufweisen [21]. Eine Studie mit Schülerinnen und Schülern im Alter von 13 bis 18 Jahren in Schweden stellt dar, dass die Heranwachsenden -und hier insbesondere Mädchen mit Behinderung und Mehrfachbehinderung eine schlechtere psychische Gesundheit berichten als Jugendliche ohne Behinderung.…”
Section: Gesundheit Von Kindern Und Jugendlichen Mit Beeinträchtigungenunclassified
“…In some countries, the prevalence of comorbidities in persons with IDD is reportedly high (Platt et al 2018;Buckley et al 2020). Although a meta-analysis showed that the prevalence of IDD is almost twice as high in low-income and middle-income countries, the number of studies addressing the comorbidities of IDD in these countries is relatively small (Maulik et al 2011).…”
Section: Introductionmentioning
confidence: 99%